Free Nutritious Food (FNF) Policy: A Political Economy Analysis and Its Impact on Community Welfare - Rina Kurniawati; Lia Muliawaty; Kamal Alamsyah (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study analyzes the Free Nutritious Food (FNF) policy from a political economy perspective and evaluates its impact on community welfare, using a case study at Junior High School 1 Cikalongkulon. Grounded in Grindle’s (2017) theory of resource distribution, the study conceptualizes public policy not merely as a technical solution but as a product of negotiation among actors with differing interests and power dynamics. Employing a qualitative approach through literature review and field observation, the research investigates the formulation and implementation of the FNF policy in a rural context characterized by logistical constraints and socio-economic vulnerabilities. The findings reveal that the program contributes to improved student attendance, enhanced nutritional status, and reduced household food-related expenditures. However, persistent challenges include limited institutional coordination, inadequate cultural adaptation, and fiscal sustainability concerns. The study recommends an inclusive and participatory policy design, gender-sensitive evaluation frameworks, and robust monitoring mechanisms to ensure effective and equitable long-term implementation of school feeding initiatives. These findings provide critical insights for enhancing policy responsiveness and advancing social welfare in underserved regions.